Linked lives across borders: Economic remittances to ageing parents in Romania - Ionuț Földes (Comparative Population Studies (CPoS), 2020)
Economic support is widespread among multigenerational Romanian family units separated by national borders and plays an important role for non-migrating family members. From a political economy perspective, remittances are characteristic of such long-term kin networks, which in turn are shaped by socio-structural contexts. This study aims to analyse transfers of remittances in cash and in kind from emigrant Romanian adult children to elderly parents back home. Both forms of upward support are investigated under the lens of family practices across distance. Data from a survey (Intergenerational solidarity in the context of work migration abroad. The situation of elderly left at home) are used to examine the influence on remittances of family commitments over time and of needs and opportunities. The sample includes 2109 parent-child dyads with data provided by elderly parents from all regions of Romania. Results of the logistic regression models show that stronger familial commitments increase the likelihood of remittances in cash and remittances in kind. Findings indicate the importance of filial support before migration and of various forms of intergenerational reciprocity. Our results stress that remittances in cash are more likely to be variable compared with remittances in kind. Both forms of support are part of a much broader set of family practices and intergenerational relationships but express different understandings of filial responsibility.
urn:nbn:de:bib-cpos-2020-03en5
Keywords: 300; Remittances; Intergenerational relationships; Transnational families; Family practices